Genetic Factors in Animal Models of Intestinal Inflammation - R Balfour Sartor (Canadian Journal of Gastroenterology)
The critical importance of host genetic susceptibility in determining chronicity, aggressiveness and complications of intestinal inflammation is clearly demonstrated by studies of inbred rodents, transgenic rats and spontaneous mutants. Inbred Lewis rats challenged by purified bacterial cell wall polymers, indomethacin or small bowel bacterial overgrowth develop chronic granulomatous intestinal inflammation with fibrosis and extraintestinal manifestations, whereas Fischer (major histocompatibility complex identical to Lewis) and Buffalo rats identically stimulated demonstrate only self-limited enterocolitis with no chronic inflammation, fibrosis, granulomas or extraintestinal inflammation. Similar differential patterns of intestinal inflammation are apparent in inbred mouse strains challenged with trinitrobenzene-sulphonic acid, Citrobacter freundii or backcrossed with T cell receptor deficient (knockout) mice. The dominant role of genetic background in induction of intestinal inflammation is further documented by spontaneous colitis which develops in spontaneously mutant mice, cotton-top tamarins, human leukocyte antigen-B27/ β2 microglobulin transgenic rats and mice with targeted deletions of certain immunoregulatory cytokine and T lymphocyte genes. Identification of the immunological mechanisms of host genetic susceptibility and the genetic basis of spontaneous colitis should provide new insights into the pathogenesis of human inflammatory bowel disease.